Correlation between ion gel characteristics and performance of ionic pressure sensors. Issue 16 (7th April 2021) - Lee, Woo Young; Kim, Yong Min; Kwon, Jin Han; Moon, Hong Chul
Abstract : In this study, a convenient approach is proposed to tune the properties of ion gels by utilizing mixed ionic liquid (IL) systems. Abstract : In this study, a convenient approach is proposed to tune the properties of ion gels by utilizing mixed ionic liquid (IL) systems. Herein, a binary IL system consisting of 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([BMI][TFSI]) and 1-butyl-3-methylimidazolium hexafluorophosphate ([BMI][PF6 ]) at various compositions is employed with poly(vinylidene fluoride- co -hexafluoropropylene) (P(VDF- co -HFP)) to prepare ion gels. A higher concentration of [BMI][TFSI] results in higher ionic conductivity but lower elastic modulus of gel electrolytes, which is explained using the difference in ionic mobility of the ILs and crystallinity of the PVDF domains. Considering this correlation, the composition of mixed ILs for ion gel-based pressure sensors is optimized. The resulting ionic pressure sensor exhibits balanced performance with decent sensitivity (∼0.058 kPa −1 ) and detectable pressure range (∼75.8 kPa). The device shows excellent long-term durability (>14 000 s) without additional encapsulation. Furthermore, this pressure sensory ion gel film successfully monitors various types of external pressure, which indicates its high practical applicability. These results imply that binary IL-engineering is an easily and readily applicable strategy for adjusting ion gel performance in accordance with the desired applications.